Sex Differences in Hippocampal Damage, Cognitive Impairment, and Trophic Factor Expression in an Animal Model of an Alcohol Use Disorder - Maynard, Mark E. (Brain Struct Funct, 2017)
Compared to men, women disproportionally experience alcohol-related organ damage, including brain damage, and while men remain more likely to drink and to drink heavily, there is cause for concern because women are beginning to narrow the gender gap in alcohol use disorders (AUD). The hippocampus is a brain region that is particularly vulnerable to alcohol damage, due to cell loss and decreased neurogenesis. In the present study, we examined sex-differences in hippocampal damage following binge alcohol. Consistent with our prior findings, we found a significant binge-induced decrement in dentate gyrus (DG) granule neurons in the female DG. However, in the present study, we found no significant decrement in granule neurons in the male DG. We show that the decrease in granule neurons in females is associated with both spatial navigation impairments and decreased expression of trophic support molecules. Finally, we show that post-binge exercise is associated with an increase in trophic support and repopulation of the granule neuron layer in the female hippocampus. We conclude that sex differences in alcohol-induced hippocampal damage are due in part to a paucity of trophic support and plasticity-related signaling in females.